The energy-economic growth nexus in Latin American and the Caribbean countries: a new approach with globalisation index - Koengkan, Matheus; Fuinhas, José Alberto; Rosa, Simone Baptista (Revista Valore, 2021)
This article inaugurates the study of the energy-economic growth nexus with a new approach with the introduction of globalisation index, in ten Latin American and the Caribbean countries from 1971-2014. The Autoregressive Distributed Lag (ARDL) and the Granger causality Wald test were used as a methodology. The empirical results pointed to the existence of a bidirectional relationship between economic growth and consumption of renewable energy, a unidirectional relationship from consumption of fossil to economic growth, and a bidirectional relationship between globalisation and consumption of renewable energy. That these results help the local governments develop new policies with the purpose of increases the consumption of renewable energy and reduces environmental degradation while promoting development.